Organ-level right ventricular dysfunction with preserved Frank-Starling mechanism in a mouse model of pulmonary arterial hypertension - Wang, Zhijie (J Appl Physiol (1985), 2018)
Pulmonary arterial hypertension (PAH) is a rapidly fatal disease in which mortality is due to right ventricular (RV) failure. It is unclear whether RV dysfunction initiates at the organ level or the subcellular level or both. We hypothesized that chronic pressure overload-induced RV dysfunction begins at the organ level with preserved Frank-Starling mechanism in myocytes. To test this hypothesis, we induced PAH with Sugen + hypoxia (HySu) in mice and measured RV whole organ and subcellular functional changes by in vivo pressure-volume measurements and in vitro trabeculae length-tension measurements, respectively, at multiple time points for up to 56 days. We observed progressive changes in RV function at the organ level: in contrast to early PAH (14-day HySu), in late PAH (56-day HySu) ejection fraction and ventricular-vascular coupling were decreased. At the subcellular level, direct measurements of myofilament contraction showed that RV contractile force was similarly increased at any stage of PAH development. Moreover, cross-bridge kinetics were not changed and length dependence of force development (Frank-Starling relation) were not different from baseline in any PAH group. Histological examinations confirmed increased cardiomyocyte cross-sectional area and decreased von Willebrand factor expression in RVs with PAH. In summary, RV dysfunction developed at the organ level with preserved Frank-Starling mechanism in myofilaments, and these results provide novel insight into the development of RV dysfunction, which is critical to understanding the mechanisms of RV failure. NEW & NOTEWORTHY A multiscale investigation of pulmonary artery pressure overload in mice showed time-dependent organ-level right ventricular (RV) dysfunction with preserved Frank-Starling relations in myofilaments. Our findings provide novel insight into the development of RV dysfunction, which is critical to understanding mechanisms of RV failure.